Optimization Of Glycerol Recovery From Pretreatment Process To Produce Succinic Acid Via Anaerobic Fermentation - Nik Nor Aziati, Abdul Aziz; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2017)
This study aims to produce succinic acid from glycerol residue through anaerobic fermentation process. The optimum condition of pH, mass substrate, and temperature was determined using response surface methodology (RSM). The concentration of glycerol and succinic acid were determined using HPLC analysis. The FTIR spectrometry was applied to examine the adsorption of organic element. Optimization of fermentation condition using RSM yielded glycerol of 159.312 g/L at pH 2, 35 °C, and 110.36 g of substrate. Succinic acid was the product of fermentation by Escherichia coli type k-12 under 19.67 g/L initial glycerol concentration, 200 rpm rotational speed, and 37 °C. The fermentation with treated glycerol generated 0.66983 g/L of succinic acid, compared to commercial glycerol which generated 0.73337 g/L of succinic acid. Overall, this research show that glycerol waste can be used as the carbon source to produce succinic acid by implementing fermentation of Escherichia coli type k-12. From the fermentation process, succinic acid was not the major product. Further study in genetic modification of Escherichia coli is highly suggested to produce succinic acid as the major product, as well as to improve the fermentation process.